GRAFOS EXPANSORES EN CRIPTOGRAFÍA – PARTE II - DARÍO ALEJANDRO GARCÍA (Revista Ingeniería, Matemáticas y Ciencias de la Información)
Expansion graphs are a class of graphs that have two apparently contradictory properties: they are sparse and wellconnected. These graphs have important applications in computer science, such as the construction of optimized networkconfigurations and, as we will see later, the construction of good graph-based summary functions.